Non-pharmacological therapies for quality of life in women with breast cancer: a protocol for a systematic review and network meta-analysis - Meng Tian; Deqi Zhang; Tianwei Lou (BMJ Open)
Introduction Breast cancer (BC) is the most frequently diagnosed cancer worldwide. Both the disease itself and the side effects of its treatments significantly impair the quality of life (QoL) of women with BC. Non-pharmacological therapies (NPTs), including exercise therapies, mindfulness-based interventions, cognitive therapies, acupoint therapies, and other complementary therapies, are increasingly being employed to improve the QoL for women with BC. However, the effects and acceptability of NPTs may vary depending on the treatment phases (intra-treatment and post-treatment) of the women with BC. This systematic review and network meta-analysis aims to compare the effects and acceptability of NPTs among women with BC across different treatment phases.Methods Relevant randomised controlled trials will be systematically searched in 7 databases, including the Cochrane Library, Embase, PubMed, Web of Science, China National Knowledge Infrastructure, China Biomedical Literature Database, and Wanfang, covering the period from their inception to February 2025. Two researchers will independently assess the risk of bias using the Cochrane Risk of Bias Tool for Randomised Trials 2.0. The network meta-analysis will be conducted using STATA 16.0. The assessments of heterogeneity, inconsistency, publication bias, evidence quality and sensitivity analysis will also be conducted. The subgroup network meta-analysis will be conducted based on the treatment phases of women with BC.Ethics and dissemination This protocol does not need approval from an ethics committee, as it is conducted based on previous research data. The results will be disseminated via peer-reviewed publications.Prospero registration number PROSPERO CRD42023476312.